2012
DOI: 10.1002/jbmr.1807
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin antibody inhibits skeletal deterioration due to reduced mechanical loading

Abstract: Sclerostin, a product of the SOST gene produced mainly by osteocytes, is a potent negative regulator of bone formation that appears to be responsive to mechanical loading, with SOST expression increasing following mechanical unloading. We tested the ability of a murine sclerostin antibody (SclAbII) to prevent bone loss in adult mice subjected to hindlimb unloading (HLU) via tail suspension for 21 days. Mice (n = 11–17/group) were assigned to control (CON, normal weight bearing) or HLU and injected with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
89
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 29 publications
17
89
0
Order By: Relevance
“…Prior studies in rodents have reported increases in SOST/ sclerostin in bone tissue (10) and in circulating sclerostin (19) during unloading. In addition, increased circulating serum sclerostin levels with a concurrent reduction of PTH levels have been reported in the context of disuse-induced bone loss in rodents (55) and humans (17).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Prior studies in rodents have reported increases in SOST/ sclerostin in bone tissue (10) and in circulating sclerostin (19) during unloading. In addition, increased circulating serum sclerostin levels with a concurrent reduction of PTH levels have been reported in the context of disuse-induced bone loss in rodents (55) and humans (17).…”
Section: Discussionmentioning
confidence: 87%
“…SOST/sclerostin expression increases with mechanical unloading (10,17) and decreases with loading (10). In addition, SOST knock-out mice are resistant to disuse-induced bone loss (18), and mice treated with sclerostin antibody show an anabolic response in the hind limb unloaded model (19). Furthermore, serum sclerostin is significantly increased during prolonged (90-day) bed rest in healthy volunteers (17), in obese patients undergoing weight loss (20), and acutely in postmenopausal stroke patients (21).…”
mentioning
confidence: 99%
“…This failure criterion was found to predict failure force values that were strongly correlated with experimental failure forces of cadaveric radii 18 and is commonly used in mFEA studies of mouse bone. 29,30 The FE models had between 676 000 and 989 000 elements with 901 000 to 1 253 000 nodes requiring a wall-clock time between 23 min and 48 min to solve and perform all post-processing on an HP BL870c system with two quad-core GHz Intel Itanium processors and 32 GB of RAM per blade server. To verify that the mesh density associated with 12 mm isotropic voxels did not inadvertently affect the predictive ability of the analyses, each element in FE models was divided into eight elements (6.0 Â 6.0 Â 6.0 mm 3 ), and the mFEA models were re-run with an inhomogeneous material definition (described in the next section).…”
Section: Methodsmentioning
confidence: 99%
“…24 Moreover, mFEA of excised bones is non-destructive allowing for subsequent histological analysis. Although a number of studies involving rodents have used mFEA to determine the effect of drug treatment on bone strength, [25][26][27][28][29][30] there is little evidence in the literature establishing that mFEA can accurately predict the mechanical properties of rodent bone, and especially murine bones. Of the few studies comparing FEA predictions to experimental measurements of strength in rodent tissues, long bones were tested with limited examination of material definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Sclerostin is emerging as a promising therapeutic target in bone disease therapy (43). Various animal studies demonstrated that the sclerostin antibody was effective in preventing unloading-induced osteoporosis (44,45). Thus, it can be hypothesized that anti-sclerostin treatment may be able to protect against occlusal hypofunction-induced alveolar bone loss, and its application in dental prosthetic rehabilitation may be promising.…”
Section: B a C Dmentioning
confidence: 99%